Correlation of Risser sign, radiographs of hand and wrist with the histological grade of iliac crest apophysis in girls with adolescent idiopathic scoliosis - Wang, William Wei Jun; Xia, Cai Wei; Zhu, Feng; Zhu, Ze Zhang; Wang, Bin; Wang, Shou Feng; Yeung, Benson Hiu Yan; Lee, Simon Kwong Man; Cheng, Jack Chun Yiu; Qiu, Yong (Spine (Philadelphia, Pa. 1976), 2009)
A correlation analysis between histologic grade (HG) of iliac crest apophysis and skeletal age assessments. To study the correlation between HGs of iliac crest apophysis and the skeletal age of hand and wrist, digital skeletal age (DSA), and Risser sign in the girls with adolescent idiopathic scoliosis (AIS). The evaluation of the remaining growth of the patients clinically and radiologically is highly significant in predicting the curve progression and thus influencing the treatment strategy in AIS. Fifty-three AIS girls with a mean age of 14.0 years undergoing corrective posterior spinal surgery and instrumentation with autogenous bone graft were recruited. Menarche status was recorded while the skeletal age of hand and wrist, DSA, and Risser grade were evaluated radiologically. Using a standardized HG of proliferative chondrocyte zone of the iliac crest apophysis, correlation between the HGs and the radiologic and clinical skeletal maturity parameters was analyzed. The HGs were negatively correlated with the radiologic parameters with the highest correlation coefficient between HGs and skeletal age of hand and wrist. The negative correlation between HGs and the 2 clinical parameters was significant and could be enhanced by combining with the radiologic parameters. No proliferative chondrocyte zone of the apophysis was detected when patients were either over 16 years of skeletal age or Risser grade 5, as well as 2-year postmenarche or over 15 years of chronological age in patients with DSA stage III and Risser grade 4. Radiologic skeletal age of the wrist and digits can provide important information for maturity assessment in girls with AIS. It can also enhance the sensitivity of clinical parameters in determining the remaining growth potential.